2009
DOI: 10.1016/j.virol.2009.01.044
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ NK cells can be productively infected with HIV, leading to downregulation of CD4 expression and changes in function

Abstract: NK cells mediate the innate immune response, and HIV-infected individuals demonstrate altered NK cell phenotype and function. We find that CD4+ NK cells are susceptible to HIV infection; this could account for the NK cell dysfunction seen in HIV-infected individuals. CD4+ NK cells express CXCR4 and can be infected with X4-tropic viruses and some primary R5-utilizing viral isolates. Treatment with the CXCR4 ligands AMD3100 and SDF-1α partially blocks infection with X4-tropic virus, treatment with anti-CCL Igs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…HIV SS DNA was identified in three (73, 157, and 858 copies/million NK cells) of four separate viremic HIV-infected subject NK cell fractions (Ͼ99% purity). We have previously described an in vitro system of NK cell HIV infection (6). In the latter system, HIV p24 expression was found in 10 to 20% of NK cells.…”
Section: Impaired Nk Cell Response To Ifn-␣ Is Not the Results Of Dimimentioning
confidence: 99%
“…HIV SS DNA was identified in three (73, 157, and 858 copies/million NK cells) of four separate viremic HIV-infected subject NK cell fractions (Ͼ99% purity). We have previously described an in vitro system of NK cell HIV infection (6). In the latter system, HIV p24 expression was found in 10 to 20% of NK cells.…”
Section: Impaired Nk Cell Response To Ifn-␣ Is Not the Results Of Dimimentioning
confidence: 99%
“…In this regard, NK cells express HIV-1 receptor and co-receptors such as CD4, CXCR4/CCR5 and Siglec-7 [42, 6264], thus implying that a direct interaction between NK cells and HIV-1 occurs. However, controversial results were obtained regarding the susceptibility of NK cells to be targeted by HIV-1 since the existence of both viral latency and productive HIV-1 infection of human NK cells has never been demonstrated ex-vivo [22] but only in-vitro [62, 63]. …”
Section: Nk Cells and Hiv-1 Pathogenesismentioning
confidence: 99%
“…A study in non-human primates however suggests a considerably shorter half life for this cell type in vivo [67]. Natural killer cells are cytotoxic lymphocytes that function as part of the innate immune system and they can be infected with HIV-1 ex vivo [68]. Valentin et al found HIV-1 DNA in natural killer cells isolated from participants on ART and recovered replication-competent virus in an outgrowth assay [69].…”
Section: Innate Immune Cells Harbour Latent Hiv-1mentioning
confidence: 99%